Supraphysiological estradiol levels on the hCG trigger day are associated with SGA for singletons born from fresh embryo transfer. (11th April 2022) - Zhang, Junwei; Du, Mingze; Sun, Lijun
Abstract: The effects of supraphysiological estradiol (E2 ) on neonatal outcomes and the significance of specific E2 concentrations remain unclear. The purpose of this study was to investigate whether supraphysiological E2 levels on the human chorionic gonadotropin (hCG) trigger day are associated with small size for gestational age (SGA) in singletons born from fresh embryo transfer (ET) cycles. Patients with singleton pregnancies who delivered after the transfer of fresh embryos, during the period from July 2012 to December 2017, at our center were included. We excluded cycles involving a vanishing twin, maternal age >35 years, basal follicle-stimulating hormone ≥10 mIU/ml, or anti-Müllerian hormone ≤1 ng/ml. We then divided all cycles into five groups by E2 level on trigger day: group A, <2000 pg/ml (reference group); group B, 2000 pg/ml≤E2 <2999 pg/ml; group C, 3000 pg/ml≤E2 <3999 pg/ml; group D, 4000 pg/ml≤E2 <4999 pg/ml; and group E, ≥5000 pg/ml. The prevalence of SGA among singletons from fresh ET was the primary outcome. The SGA rate significantly increased when the E2 level was ≥4000 pg/ml, as observed by comparing groups D (odds ratio [OR]: 1·79, 95% confidence interval [CI]: 1·16–2·76, P = 0·01) and E (OR: 1·68, 95% CI: 1·10–2·56, P = 0·02) with the reference group. Multivariate logistic regression indicated that a serum E2 level of at least 4000 pg/ml on the hCG trigger day was associated with increased SGA and with significant differences for groups D (adjusted OR [AOR]: 1·65, 95% CI: 1·05–2·59, P = 0·03) and E (AOR: 1·60, 95% CI: 1·03–2·53, P = 0·04) relative to the reference group. In conclusion, in fresh ET cycles, the supraphysiological E2 ≥4000 pg/ml on the hCG trigger day increases the risk of SGA.